In vitro and in vivo studies of Mg-30Sc alloys with different phase structure for potential usage within bone. (15th October 2019) - Liu, Jianing; Lin, Yulin; Bian, Dong; Wang, Ming; Lin, Zefeng; Chu, Xiao; Li, Wenting; Liu, Yang; Shen, Zhenquan; Liu, Yinong; Tong, Yunxiang; Xu, Zhigang; et al.
Graphical abstract: Abstract: Proper alloying magnesium with element scandium (Sc) could transform its microstructure from α phase with hexagonal closed-packed (hcp) structure into β phase with body-cubic centered (bcc) structure. In the present work, the Mg-30 wt% Sc alloy with single α phase, dual phases (α + β) or β phase microstructure were developed by altering the heat-treatment routines and their suitability for usage within bone was comprehensively investigated. The β phased Mg-30 wt% Sc alloy showed the best mechanical performance with ultimate compressive strength of 603 ± 39 MPa and compressive strain of 31 ± 3%. In vitro degradation test showed that element scandium could effectively incorporate into the surface corrosion product layer, form a double-layered structure, and further protect the alloy matrix. No cytotoxic effect was observed for both single α phased and β phased Mg-30 wt% Sc alloys on MC3T3 cell line. Moreover, the β phased Mg-30 wt%Sc alloy displayed acceptable corrosion resistance in vivo (0.06 mm y −1 ) and maintained mechanical integrity up to 24 weeks. The degradation process did not significantly influence the hematology indexes of inflammation, hepatic or renal functions. The bone-implant contact ratio of 75 ± 10% after 24 weeks implied satisfactory integration between β phased Mg-30 wt%Sc alloy and the surrounding bone. These findings indicate a potential usage of the bcc-structured Mg-Sc alloy within bone and might provide a new strategy for future biomedical magnesium alloy design. Statement of Significance: Scandium is the only rare earth element that can transform the matrix of magnesium alloy into bcc structure, and Mg-30 wt%Sc alloy had been recently reported to exhibit shape memory effect. The aim of the present work is to study the feasibility of Mg-30 wt%Sc alloy with different constitutional phases (single α phase, single β phase or dual phases (α + β)) as biodegradable orthopedic implant by in vitro and in vivo testings. Our findings showed that β phased Mg-30 wt%Sc alloy which is of bcc structure exhibited improved strength and superior in vivo degradation performance (0.06 mm y −1 ). No cytotoxicity and systematic toxicity were shown for β phased Mg-30 wt%Sc alloy on MC3T3 cell model and rat organisms. Moreover, good osseointegration, limited hydrogen gas release and maintained mechanical integrity were observed after 24 weeks' implantation into the rat femur bone.